Slavery remembered : a record of twentieth-century slave narratives - Escott, Paul D., 1947- (The University of North Carolina Press, 1979)
This is the first major attempt to analyze the slave narratives in the Federal Writers' Project. Escott read nearly 2,400 narratives to establish 81 categories of information for computer analysis. Tables presenting this data are set within a well-organized text that includes many quotations. Slavery remembered is an important contribution to the study of American slavery and, because of its brevity and clarity, an ideal classroom text for American history surveys as well as more specialized courses.